Experience of dog-assisted education as a pedagogical tool in university classrooms - Suárez Ramírez, José Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This research has been carried out with the presence of an Assisted Education dog in a university classroom for five sessions in 2021. The objective is to study the benefits it has on the working environment (reduction of stress) by increasing attention, concentration and level of participation. The methodology is descriptive. Two surveys were carried out (initial and final) based on theory with quantitative items, according to the Likert scale, and qualitative items. The results obtained reflect a decrease in stress, a benefit in the work environment, and an increase in attention.